Distribution and seasonal variation of picoplankton in Sanggou Bay, China - L Zhao (Inter-Research, 2016)
Picoplankton abundance and biomass in Sanggou Bay, China, were investigated in 4 successive seasons (April, August and October 2011, January 2012). Different distribution patterns of picoplankton abundance and biomass were observed according to season and culture areas (bivalves or macroalgae). Synechococcus, picoeukaryotes and heterotrophic prokaryotes exhibited higher abundance and biomass in warm seasons (summer and autumn) than in cold seasons (spring and winter). Over all 4 seasons, picoplankton abundance was higher in the bivalve culture area than in the macroalgae culture area. Among picoplankton, picoeukaryotes contributed most to the carbon standing stock in summer and autumn. In spring and winter, the heterotrophic component biomass exceeded that of the autotrophic picoplankton. Picoeukaryotes were an important contributor (21-27%) to total phytoplankton carbon biomass in spring to autumn. In spring, heterotrophic prokaryote biomass accounted for more than 56% of total phytoplankton biomass, and even exceeded phytoplankton biomass at some stations. As revealed by multiple stepwise regression analysis, physicochemical factors and protist grazing were the most important variables that controlled picoplankton distribution and variation. The reduction in grazing pressure, as well as phosphorus release by bivalves, is likely to explain the higher abundance of picoplankton in the bivalve culture area of Sanggou Bay.